Peningkatan Perekonomian Warga Kurang Mampu melalui Pengadaan Tempat Usaha Kios Kelontong - Adityo Noor Setyo Hadi Darmo; Nur Hayati; Faiz Listyanda (Jurnal Masyarakat Indonesia (Jumas), 2024)
The existence of home industry plays a very important role in empowering small and medium-sized communities so that they as business actors have independence and self-confidence in entrepreneurship to help the family economy. This Community Service aims to help increase the economic value of small business owners' families by providing kiosks as permanent business premises so that the layout and service are better and compared to previous kiosks/grocery stores which were managed conventionally. The service activities were carried out by the service team together with residents who live in the surrounding areas, starting with conducting site surveys, followed by procurement of row materials in the form of harbel, river sand, cement and lime. Carrying out activities in order to obtain optimal output results, during the activity process stages, assistance is provided with work by the service team starting from preparation for demolition, installation of building foundations, harbel walls, building framework to the finishing process. The impact of good cooperation between partners, the surrounding community and the service team can result in a permanent kiosk building that is suitable, safe and comfortable to be used as a grocery store business to meet the needs of the surrounding residents.